Spinning into Control Improvising the Sustainable Startup - Kornel, Amiel (Palgrave Macmillan US, 2018)
Could everything we've learned about entrepreneurship simply be wrong? There is no shortage of how-to books with 'manual' in the title, and articles promising 'The 7 [or 6 or 10] key traits of successful entrepreneurs', which breed an infectious optimism all too often quashed as startups fail. Amiel Kornel puts a persuasive case for an alternative theory that while grounded in the natural way great entrepreneurs operate resists reduction to a simple recipe or method. Kornel, who has coached hundreds of entrepreneurs, believes that disciplined planning, lean management, and commitment are no guarantee of success. The limited resources of a startup demand knowing when and how to explore and 'tinker', artfully recombining ideas, designs, media, software, and materials on hand. True venture craftsmen harness and redirect the energy of startups that might otherwise spin dangerously out of control towards failure. The stories of entrepreneurs like Sun Basket's Adam Zbar, Minecraft's Markus Persson, Y Combinator's Paul Graham, and Metacode Technologies' Joel Schatz are woven throughout the book, along with examples from beyond business, including legendary ocean-racing sailor Isabelle Autissier and acclaimed urban designer Gerard Penot. Kornel shows how meeting challenges in a broad variety of fields rife with uncertainty often relies on the ability to loosen the coupling between command and control, a prerequisite of skillful improvisation.